Primary Multiple Giant Hydatid Cyst of the Liver: A Case Report - Ozgur Turk; Hasan Polat; Bartu Badak (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Hydatid cyst is a parasitic infection of liver. One of frequent reason of liver mass is hydatid cyst in tropical and rural countries. In some cases rapidly grow up of cyst mimic liver masses. A sixty years old female admitted our hospital with abdominal pain. Abdominal ultrasound showed 74x75 mm in segment two, 115x91 mm in segment six and 115x62 mm in segment four type four hydatid cysts. Patient was admitted for surgery; pericystectomy and omentoplasty performed. In multiple cysts surgical management is sometimes difficult. It is better to drain all the cysts at the same time. Surgical interventions can prevent complications and spread of Echinococcosis also gives chance of curative treatment.